As Camp as a Row of Pink Tents: Stephen’s Portrait of Mr W. S. - Samuel Slote (Open Library of Humanities)
In the ‘Scylla and Charybdis’ episode of Ulysses, Stephen Dedalus presents a theory about Shakespeare’s biographical motivations for writing Hamlet, which he ultimately claims, perhaps disingenuously, to not believe. Stephen’s apparent disbelief in his own theory echoes Oscar Wilde’s ‘Portrait of Mr W. H.’, which is referenced within ‘Scylla’, and which also propounds a theory of Shakespeare’s artistic production in terms of his biography. Furthermore, like the various characters in Wilde’s story, Stephen’s theory is propelled primarily from the internal evidence of Shakespeare’s texts. In this article, I will analyse the playful and learned insincerity of both theories through the optic of camp in order to tease out the implications that Stephen’s argument about Shakespeare has for James Joyce’s aesthetics.